2009
DOI: 10.1111/j.1574-6968.2008.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine and citrulline do not stimulate growth of twoOenococcus oenistrains in wine

Abstract: Arginine metabolism by wine lactic acid bacteria (LAB) may lead to wine quality degradation. While arginine is essential for growth of the wine relevant LAB Oenococcus oeni, it remains unclear whether it also stimulates its growth. This study evaluated the effect of arginine and citrulline, the partially metabolized intermediate of the arginine deiminase pathway, on the growth of two commercial O. oeni strains in comparison with a Lactobacillus buchneri strain in wine and at wine pH values. Neither arginine no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Recently, it has been also reported that citrulline degradation is higher in O . oeni grown at low pH, suggesting that the physiological role of the ADI pathway in this species may lie in enhanced adaptation of cells to acidic environments 36. It has also been demonstrated that the production of OTC was induced during the development of adaptative acid tolerance response in Lactococcus lactis 37.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, it has been also reported that citrulline degradation is higher in O . oeni grown at low pH, suggesting that the physiological role of the ADI pathway in this species may lie in enhanced adaptation of cells to acidic environments 36. It has also been demonstrated that the production of OTC was induced during the development of adaptative acid tolerance response in Lactococcus lactis 37.…”
Section: Resultsmentioning
confidence: 97%
“…O. oeni possesses the arc genes (Araque et al, 2009) and therefore, arginine would stimulate O. oeni growth and resistance in wine, which was reported by Bourdineaud (2006). Nevertheless, some other studies reported that arginine does not stimulate growth of O. oeni in wine under standard MLF conditions (Terrade and Mira de Orduña, 2009). Our results support that arginine and glucose enhance bacterial growth and resistance to ethanol by utilizing the sugar and the ADI pathway for arginine degradation to obtain energy and overcome the stress due to the presence of ethanol in their growth medium.…”
Section: B) C)mentioning
confidence: 84%
“…Vrancken et al (2009) demonstrated in a strain of Lactobacillus fermentum that the ratio between citrulline and ornithine and the pattern of their formation from arginine degradation showed variation as function of environmental pH. The not detection of citrulline in presence of arginine at low pH by ammonia-positive strains is an important fact considering that citrulline is a direct precursor of carcinogenic EC (Terrade and Mira de Orduna 2008). Citrulline is apparently the main EC precursor produced by Lactobacillus hilgardii strains in spoiled, fortified wine (Azevedo et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…It is interesting to note that among strains that produced ammonia from arginine, only arginine stimulated growth of Lactobacillus brevis M15 and Leuconostoc dextranicum M13 under conditions studied, suggesting effective energy coupling from arginine degradation to growth. Terrade and Mira de Orduna (2008) reported that neither arginine nor citrulline increased growth of two Oenococcus oeni strains in comparison with one Lactobacillus buchneri strain. However, arginine and citrulline were partially degraded in all incubations for both Oenococcus oeni.…”
Section: Discussionmentioning
confidence: 97%